2005
DOI: 10.1038/sj.npp.1300967
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Neurodevelopmental Effects of Dexamethasone Modeled in PC12 Cells: Identifying the Critical Stages and Concentration Thresholds for the Targeting of Cell Acquisition, Differentiation and Viability

Abstract: The use of dexamethasone (DEX) to prevent respiratory distress in preterm infants is suspected to produce neurobehavioral deficits. We used PC12 cells to model the effects of DEX on different stages of neuronal development, utilizing exposures from 24 h up to 11 days and concentrations from 0.01 to 10 mM, simulating subtherapeutic, therapeutic, and high-dose regimens. In undifferentiated cells, even at the lowest concentration, DEX inhibited DNA synthesis and produced a progressive deficit in the number of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 60 publications
5
36
0
Order By: Relevance
“…Dex completely blocked the NGF-induced effect on cell proliferation while partially affected the neurite extension but not the percentage of cells responding to NGF; thus reinforcing recent similar neurotoxic effects in Dex-treated PC12 cells [41], or hyppocampal neurons [42,43]. Since Dex treatment induced additional cellular effects such as downregulation of MAP-2, crucial for NGF-induced neurite outgrowth [23], it also appear plausible that Dex inhibits the expression of proteins necessary for TrkA-mediated neurite outgrowth which would uncouple the TrkA activity from neurite outgrowth.…”
Section: Discussionmentioning
confidence: 61%
“…Dex completely blocked the NGF-induced effect on cell proliferation while partially affected the neurite extension but not the percentage of cells responding to NGF; thus reinforcing recent similar neurotoxic effects in Dex-treated PC12 cells [41], or hyppocampal neurons [42,43]. Since Dex treatment induced additional cellular effects such as downregulation of MAP-2, crucial for NGF-induced neurite outgrowth [23], it also appear plausible that Dex inhibits the expression of proteins necessary for TrkA-mediated neurite outgrowth which would uncouple the TrkA activity from neurite outgrowth.…”
Section: Discussionmentioning
confidence: 61%
“…Importantly, each of the mechanisms made a partial contribution to the net outcome for either neural cell replication or differentiation. Cholinergic antagonists, although totally ineffective in preventing the antimitotic effects of CPF in undifferentiated cells (Song et al 1998), were successful once differentiation was under way, in partially reversing the deficits in cell number and the rise in protein/DNA ratio; this is entirely consistent with the transition to a cholinergic phenotype in PC12 cells (Jameson et al 2006a, 2006b; Teng and Greene 1994) and with the increasing role of cholinergic mechanisms in the adverse effects of CPF in vivo as brain development progresses (Slotkin 1999, 2004, 2005; Whitney et al 1995). Nicotine was partially effective in protecting cell replication in undifferentiated cells but likely through antioxidant actions (Qiao et al 2005), so that a similar effect was found with vitamin E. With increasing differentiation, the effects of nicotine acting as a cholinergic agonist offset some of the positive consequences of its antioxidant actions, so that the remaining beneficial effect depended on whether the CPF concentration was low or high.…”
Section: Discussionmentioning
confidence: 85%
“…In the present study, we examined the effects of CPF with and without each of the ameliorating treatments on both undifferentiated and differentiating PC12 cells with regard to DNA synthesis, indices of cell number and size, and AC signaling. Because each neural cell contains a single nucleus, we measured DNA content to evaluate the number of cells (Winick and Noble 1965) and the protein/DNA ratio as an index of cell size (Abreu-Villaça et al 2005; Jameson et al 2006a; Slotkin et al 2007; Song et al 1998). For AC measurements, we evaluated basal enzymatic activity, the response to global stimulation of G-proteins by fluoride, and maximal enzymatic activity elicited by forskolin, which acts directly on AC, bypassing the need for activation of neurotransmitter receptors or G-proteins (Seamon and Daly 1986).…”
mentioning
confidence: 99%
“…Each neural cell contains only a single nucleus (Winick and Noble 1965), so that the DNA content (micrograms of DNA per culture dish in the present study) reflects the total number of cells (Song et al 1998). Indices of growth were provided by measurements of protein subfractions related to cell size and membrane surface area (Jameson et al 2006a; Thai et al 1996). The total protein/DNA ratio rises with cell enlargement, and the membrane/total protein ratio falls as a consequence of the decreased surface-to-volume ratio.…”
mentioning
confidence: 99%
“…On the other hand, with the onset of differentiation, the development of neuritic projections necessitates a rise in the relative contribution of membrane proteins, so that the increase in the membrane/total protein ratio gives an indication of augmented membrane “complexity.” The effects on cell number, size, and cell surface area were compared to those on viability (evaluated by trypan blue exclusion) and lipid peroxidation (evaluated by thiobarbituric acid-reactive species; TBARS). To characterize the catecholaminergic and cholinergic phenotypes, we assessed the ratio of activities of tyrosine hydroxylase (TH) to choline acetyltransferase (ChAT), the respective biosynthetic enzymes for dopamine and acetylcholine (Teng and Greene 1994; Jameson et al 2006a, 2006b). …”
mentioning
confidence: 99%